The Impact of Augmented Reality-based Learning Media on Primary Students' Retention of Human Sensory System Concepts - Rosita, Desyi; Dewanti, Sintha Sih; Ibrahim, Ibrahim (Journal of Integrated Elementary Education, 2025)
The use of Augmented Reality (AR) in education contexts has great potential to enhance students’ learning experiences and retention for abstract scientific content. This research was conducted to find out whether AR-based learning media is effective in increasing the retention of elementary school students on the five human senses. The study used a quantitative one-group pretest-posttest design with 52 4th-grade students of two Islamic elementary schools located in Pandeglang, Indonesia. AR media was applied to present 2D and 3D interactive visuals for introducing science content. Data were collected from pre-test, post-test, and documents, then analyzed by using a paired sample t-test in SPSS 16. A statistically significant difference is found between posttest and pretest scores (p < 0.05), indicating that the retention of AR media among students was effective. The AR media-using students showed a higher level of conceptual understanding and memory for the topic of the five senses. In this paper, we stress the potential of AR technology as a transforming tool, shedding new light on how science teaching can be transformed into an innovative and efficient learning model. It also contributes to the growing body of research on educational technology in primary education, especially in the Indonesian context. The findings provide significant implications for educators, curriculum designers, and education policy makers in balancing the introduction of the latest digital technologies into the primary classroom to enhance students’ learning.